The Development of Student Worksheets (LKPD) Based on Islamic Characteristics in Mathematics Fractional Materials in Elementary School - Nasywa Hilmi; Sapri Sapri (Universitas Pahlawan Tuanku Tambusai, 2022)
Education has a big influence on the development of the quality of human resources. LKPD based on Islamic character is believed to contribute to the formation of the character of students. This LKPD is applied to third grade students of SD Islam Darul Mustafa Medan on fractions. The purpose of this research is to develop LKPD based on Islamic character that is valid, practical, effective in increasing the knowledge and Islamic character of students by using research development (Research and iDevelopment). This Research and Development uses the ADDIE model. The design of this study used the experimental design of One Group Pretest Posttest Design. The pre and post test data were processed to determine the increase in understanding of the concept, while the results of observations and attitude scales were processed to determine the increase in personality values between individual students. The results of the study the average value of the observed N-gain Score according to Hake, R.R, 1999, which means 92.976190476 or 93% is included in the effective category, indicating that the use of LKPD based on Islamic character is in the high category in increasing the effectiveness of student learning.